Microscale Testing in Aquatic Toxicology Advances, Techniques, and Practice - Wells, Peter G.; Lee, Kenneth; Blaise, Christian (Taylor & Francis, 1998)
Bioassays are among the ecotoxicologist's most effective weapons in the evaluation of water quality and the assessment of ecological impacts of effluents, chemicals, discharges, and emissions on the aquatic environment. Information on these assessment aids is needed throughout the international scientific and environmental management community. This comprehensive reference provides an excellent overview of the small-scale aquatic bioassay techniques and applications currently in use around the world. This special volume is the result of several years of collaboration between Environment Canada and Fisheries and Oceans Canada. Internationally recognized research scientists at many institutions have contributed to this state-of-the-art examination of the exciting, environmentally important field of microscale testing in aquatic toxicology. Microscale Testing in Aquatic Toxicology contains over forty chapters covering relevant principles, new techniques and recent advancements, and applications in scientific research, environmental management, academia, and the private sector.